The Advantages of Qur’an Memorization Toward Children’s Social-Emotional Development - Fairuzillah, Muhammad Naufal; Dirgantara, Yudi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This study is a literature review aimed to discover the advantages of Qur’an memorization toward children’s social-emotional development. Collective morality and social-emotional values are contained in the Qur’an. Several advantages of Qur’an memorization toward children’s social-emotional development are: listening to the Qur’an recitation helps to reduce anxiety/stress and to produce relaxation, memorizing the Qur’an tends to develop social competencies, memorizing the Qur’an supports self-control memorizing the Qur’an encourages persistence. However, parents or teachers should be concerned about their children’s characteristics. Therefore, the implementation of Qur’an memorization for children should be in accordance with the children's learning abilities and development. Parents can optimize the social-emotional advantages of their children through learning and memorizing the Qur’an if they apply the appropriate Qur’an memorization strategies to their children.